Atrial Fibrillation Known Before or Detected After Stroke Share Similar Risk of Ischemic Stroke Recurrence and Death. Issue 5 (May 2019) - Yang, Xiao-Meng; Rao, Zhen-Zhen; Gu, Hong-Qiu; Zhao, Xing-Quan; Wang, Chun-Juan; Liu, Li-Ping; Liu, Chelsea; Wang, Yi-Long; Li, Zi-Xiao; Xiao, Rui-Ping; Wang, Yong-Jun
Abstract : Background and Purpose—: We aim to compare the risk of 1-year ischemic stroke recurrence and death for atrial fibrillation diagnosed after stroke (AFDAS), atrial fibrillation known before stroke (KAF), and sinus rhythm (SR). Methods—: From June 2012 to January 2013, 19 604 patients with acute ischemic stroke were admitted to 219 urban hospitals in the China National Stroke Registry II. Based on heart rhythm assessed during admission, we classified patients as AFDAS, KAF, or SR. We explored the relationship between heart rhythm groups and 1-year ischemic stroke recurrence or death by using Cox regression adjusted for multiple covariates. Considering that death is a competing risk for stroke recurrence, we used the competing risks analysis of Fine and Gray and subdistribution Cox proportional hazards to test the association between heart rhythm and 1-year outcomes. Results—: Among 19 604 ischemic stroke patients, 17 727 had SR, 495 AFDAS, and 1382 KAF. At 1 year, 54 (10.9%) patients with AFDAS, 182 (13.2%) with KAF, and 1008 (5.7%) with SR had recurrent ischemic strokes ( P <0.0001). Mortality was 22.0% in patients with AFDAS, 22.1% in patients with KAF, and 7.0% in patients with SR ( P <0.0001). AFDAS-related ischemic stroke recurrence adjusted risk was higher than that of SR (adjusted subdistribution hazard ratios, 1.61; 95% CI, 1.29–2.01) but not different from that of KAF (adjusted subdistribution hazard ratio, 1.12; 95% CI, 0.87–1.45]). The adjusted risk of 1-year death for AFDAS was also higher than that of SR (hazard ratio, 1.70; 95% CI, 1.37–2.12) and not different from that of KAF (hazard ratio, 1.10; 95% CI, 0.86–1.41). Conclusions—: This study showed that AFDAS had similar risk of 1-year ischemic stroke recurrence and mortality when compared with KAF and higher risk when compared with SR. The potential risk of AFDAS should be given more emphasis, and appropriate treatment is needed to achieve reduction in the incidence of stroke recurrence and mortality. Abstract : Supplemental Digital Content is available in the text.